2013
DOI: 10.4236/ijcns.2013.612055
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation in Stochastic Dynamic Systems—Survey and New Results IV: Seeking Minimum of API in Parameters of Data

Abstract: This paper investigates the problem of seeking minimum of API (Auxiliary Performance Index) in parameters of Data Model instead of parameters of Adaptive Filter in order to avoid the phenomenon of over parameterization. This problem was stated by Semushin in [2]. The solution to the problem can be considered as the development of API approach to parameter identification in stochastic dynamic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Thus, we develop the existing APA approach for the systems with the high level of uncertainty. In all previous related works [Semushin, 2011a;Semushin, 2011b;Tsyganova, 2011;Semushin and Tsyganova, 2013;Semushin, 2014;Semushin et al, 2018] it was assumed that exogenous inputs are known or they are Gaussian white noises.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we develop the existing APA approach for the systems with the high level of uncertainty. In all previous related works [Semushin, 2011a;Semushin, 2011b;Tsyganova, 2011;Semushin and Tsyganova, 2013;Semushin, 2014;Semushin et al, 2018] it was assumed that exogenous inputs are known or they are Gaussian white noises.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, for solving the parameter identification problem, we use an alternative approach that is the Active Principle of Adaptation (APA) [Semushin, 2011a;Semushin, 2011b;Semushin and Tsyganova, 2013;Semushin, 2014]. The main idea for it is to construct an auxiliary identification criterion J ε (θ) [Tsyganova, 2011;Semushin and Tsyganova, 2013;Semushin et al, 2018] which is instrumental because it depends on only directly observed values and can be minimized with the use of a known numerical optimization methods.…”
Section: Parameter Identification Problemmentioning
confidence: 99%
“…Such criteria include the well-known least squares and maximum likelihood criteria. An alternative approach is the auxiliary performance index method [18]. Thus, the algorithm of numerical minimization of the original functional (12) by the parameter θ is replaced by the algorithm of numerical minimization of the selected instrumental criterion, which is practically feasible.…”
Section: The Problem Of Parameter Identificationmentioning
confidence: 99%